Almost Contra-$(τ_1,τ_2)p$-continuity for Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new class of functions between bitopological spaces, namely almost contra-$(τ_1,τ_2)p$-continuous functions. Moreover, some characterizations and several properties concerning almost contra-$(τ_1,τ_2)p$-continuous functions are established.